Exploring Student’s Attitudes towards Mental Health Problems in Chitwan, Nepal - Acharya, Samjhana (International Research Journal of MMC, 2025)
Introduction: I investigated participants' attitudes towards mental health problems (ATMHP), considering demographic variables such as age, gender, ethnicity, religion, study levels, study fields, types of academic institutions, and familiarity with mental health problems. The aim of the study is to examine the relationship of ATMHP with various demographic variables. Methods: A cross-sectional research design was employed by using opportunity sampling, I sampled 348 participants from private, community and Government Colleges in Chitwan district. I used ATMHP scale, a reliable and valid tool in 2022. I employed descriptive and inferential statistics to examine the relationship between ATMHP and various demographic factors, as well as the differences in ATMHP across different groups. Results: I observed an overall unfavorable attitude towards mental health problems among the respondents. No significant differences were found between/among gender, ethnicity, religion, study levels, study fields, types of academic institutions, and familiarity with mental health problems in the level of ATMHP. Conclusion: I observed generally unfavorable ATMHP across the study, with no significant differences between comparison groups. Unfavorable attitudes across all groups highlight the need for inclusive mental health education and stigma-reduction efforts in colleges.